Arthroscopic Lunate Excision for Stage 3 Kienbock's Disease - Merlini, L.; Maffeis, J.; Mathoulin, C.; Sivakumar, B.S. (Journal of Wrist Surgery, 2023)
Background The ideal treatment of stage 3 Kienbock's disease is uncertain, with current open procedures conferring the risk of carpal instability, ulnar translocation, and stiffness. We present our technique of arthroscopic lunate excision, and discuss our short- to medium-term results.Description of Technique Via standard wrist arthroscopic portals, the lunate is excised using a combination of shavers, burrs, and rongeurs. Care is taken to preserve the extreme dorsal and volar cortices of the lunate to prevent carpal instability. A short arm backslab is applied for 2 weeks, after which the patient commences range of motion.Patients and Methods Consecutive patients undergoing arthroscopic lunate excision at a single center in Paris, France, underwent pre- and postoperative assessment. Parameters assessed include range of motion, as well as patient-reported outcome measures (PROMs).Results A cohort of 13 patients (7 females and 6 males with a mean age of 27.2 years) underwent arthroscopic lunate excision, and were followed up for a mean of 1.96 years. Significant improvements were noted in flexion, extension, pronation, grip strength, and PROMs.Conclusions Arthroscopic lunectomy provides significant improvements in clinical and PROMs at short- to medium-term follow-up, and conserves other salvage options in case of failure. Long-term clinical follow-up and further biomechanical studies would be beneficial.
Keywords: Kienbock's; arthroscopy; lunate; salvage; avascular necrosis